Use of force plate for acquisition of kinetic data during human gait - Barela, Ana Maria Forti (2011)
We cannot see forces and are not able to measure them during a clinical evaluation. However, the ground reaction force can be measured with a force plate, which is an instrument used for gait analysis in many laboratories. With a force plate one can acquire data that describe some gait characteristics not detectable through visual inspection. In this article, we present information regarding types of force plate commercially available, installation, data acquisition during gait, data normalization, and the interpretation of these data. It is not our intention to present a database of kinetics data from clinical analysis, but it is to provide basic subsidies to use force plate to acquire kinetics data during human gait.